Π-π stacking interface design for improving the strength and electromagnetic interference shielding of ultrathin and flexible water-borne polymer/sulfonated graphene composites. (August 2019) - Wei, Linfeng; Zhang, Wenbo; Ma, Jianzhong; Bai, Shu-Lin; Ren, Yanjuan; Liu, Chao; Simion, Demetra; Qin, Jianbin
Abstract: π-π stacking interface design strategy is proposed to prepare ultrathin and flexible water-borne polymer/sulfonated graphene nanosheets (S-GNS) composite by a facile self-assembly method in latex. The water-dispersible S-GNS was made by modifying the GNS with aryl diazonium salt. Styrene was introduced into water-borne polymer to form π-π stacking interaction with S-GNS. The composite shows good mechanical properties and high electromagnetic interference (EMI) shielding effectiveness (SE) in the X band (8.2–12.4 GHz). By Raman spectra, tensile tests, and simulation calculation, π-π stacking interaction is proved to be an effective interface bonding to enhance the mechanical properties. With a filler loading of 20 wt%, the tensile strength of composites is enhanced by 578%. The incorporation of 25 wt% S-GNS leads to a high EMI SE of 21.5 dB at 0.05 mm thickness, which remains unchanged after 1000 times bending. The specific SE/thickness (SSE/t) of the composite is as high as 2663 dB cm 2 /g, outperforming the ever reported materials with similar filler loading (25 wt%). The composite can be used as coating on the surfaces of solids, indicating the great potential for wide application. Graphical abstract: Image 1